The religious identity of young Muslim women in Berlin : an ethnographic study - Bendixsen, Synnøve K. N. (Muslim minorities, 2013)
The Religious Identity of Young Muslim Women in Berlin offers an in-depth ethnographic account of Muslim youth's religious identity formation and their everyday life engagement with Islam. It deals with the reconstruction of selfhood and the collective content of identity formation in an urban and transnational setting.